Psychological Stress and Its Relation to Academic Achievement Motivation among Married Students at University - Ghafoor, Bushra Noureddine (International Journal of Psychosocial Rehabilitation, 2020)
To facilitate life, man is thinking about finding and creating things that are unavailable before. There are thousands of examples surrounding us that demonstrate this fact. Psychological stress is a general condition having various rates in each individual within the environment in which they live. It is one of the psychological problems faced by female students, beginning from the primary to the higher levels of education. The motives are among the psychological themes that aroused the attention of many psychologists and academics. This is attributed to that they form the significant basics to study human behavior and the reasons behind it. Concerning the objectives, this research aims at defining: 1. 2. 3. The level of psychological stress among married students at university. The level of academic achievement motivation among married students at university. The statistically significant differences in relation to psychological stress and academic achievement motivation according to the gender variable. 4. The relationship between psychological stress level and academic achievement motivation among married students at university. This study is organized into four sections. Section one presents a general framework of research, such as problem, significance, objectives, limitations and definition of terms. The second section reviews the theoretical framework and the previous studies. Moreover, section three deals with research procedures through identifying research community and sample which included (100) students selected from specific colleges of Kirkuk University including: nursing, education, medicine and sciences, which were chosen randomly. Research instruments consisted of validity, reliability, the final application and statistical methods. Finally, section four discusses findings, conclusions, recommendations and suggestions. The results were as follows: 1. 2. Married students at university have psychological stress. Low level of academic achievement motivation among married students because of the psychological stressors and many responsibilities they have in order to live and upbringing children. 3. There are statistically significant differences in psychological stress and academic achievement motivation according to the gender variable. 4. There is a strong relationship between psychological stress and academic achievement motivation, i.e., the greater the respondents’ psychological pressure, the lower their level of motivation for academic achievement.